Bukti Keilahian Yesus Kristus Berdasarkan Filipi 2:6 Sebuah Jawaban Teologis Terhadap Kristologi Ebionisme, Arianisme Dan Saksi Yehuwa - Esap Veri; Gunar Sahari; Yunus Selan (STT Pelita Dunia, 2021)
Abstract: This article discusses the divinity of Jesus Christ based on Philippians 2:6 as a theological answer to the christology of Ebionism, Arianism, and Jehovah's Witnesses. The main focus in this study is to examine theologically the meaning of “the image of God” in Philippians 2:6. This paper shows the result that Philippians 2:6 is explaining the divine qualifications of Jesus Christ which means Jesus Christ before the incarnation, He has existed in eternity with the Father. So it can be said that Jesus Christ is not a creation of God or an ordinary man because Jesus Christ is the same morphe as God the Father. This paper certainly uses a qualitative method, namely a method that describes a phenomenon under study. then to describe the phenomenon under study, of course, requires literature (library review). The purpose of this paper is for the lay congregation to fully and correctly understand the teachings of the Person of Jesus Christ (Christology) in order to ward off false teachings. Abstrak: Artikel ini membahas keilahian Yesus Kristus berdasarkan Filipi 2:6 sebagai jawaban teologis terhadap kristologi Ebionisme, Arianisme, dan Saksi Yehuwa. Fokus utama dalam kajian ini yaitu mengkaji secara teologis makna “rupa Allah” dalam Filipi 2:6. Tulisan ini memperlihatkan hasil bahwa Filipi 2:6 sedang menjelaskan kualifikasi ilahi Yesus Kristus yang artinya Yesus Kristus sebelum berinkarnasi, Ia telah ada dalam kekekalan bersama dengan Bapa. Jadi dapat dikatakan bahwa Yesus Kristus bukan ciptaan Allah atau manusia biasa karena Yesus Kristus morfe yang sama dengan Allah Bapa. Tulisan ini tentu menggunakan metode kualitatif yaitu metode yang mendeskripsikan sebuah fenomena yang dikaji. maka untuk mendeskripsikan fenomena yang diteliti tentunya membutuhkan literatur-literatur (kajian pustaka). Tujuan dari tulisan ini agar jemaat khusus awam bisa memahami secara utuh dan benar mengenai ajaran tentang Pribadi Yesus Kristus (Kristologi) guna menangkal ajaran yang sesat.